A Happy Holiday : English Canadians and Transatlantic Tourism, 1870-1930 - Morgan, Cecilia, 1958- (Book collections on Project MUSE., 2008)
A Happy Holiday argues that overseas tourism offered people the chance to explore questions of identity during this period, a time in which issues such as gender, nation, and empire were the subject of much public debate and discussion.